Patterns of internal communication in the implementation of total quality management (TQM) at manufacturing organisations - Sharina Samsudin; Che Azlan Taib; Hanissah A. Razak; Rushami Zien Yusoff (Penerbit Universiti Kebangsaan Malaysia, 2021)
Organisations need to perform, productivity needs to be improved and organisations’ activities need to be more effective, especially after the world economic crisis due to the Covid-19 pandemic. Therefore, the need for quality improvements is crucial in both manufacturing and service sectors. The main purpose of this paper is to present an analysis of internal communication patterns in TQM implementation in Malaysia's manufacturing organisations. This is a multiple case study done using qualitative in-depth interview technique of data collections with 14 informants representing five large manufacturing organisations. Open-ended questions in semi-structured interviews enabled informants to describe their answers based on themes. The study has been carried out in manufacturing organisations originating from three different continents; two Malaysian local organisations, two eastern and one western organizations, and all of them located in Malaysia. In selecting the informants, the study adopts a judgment type of purposive sampling techniques. Results show that the most preferable and reliable communication medium between superiors and subordinates is still face-to-face meetings, although we are in the era of technology and IR4.0. Meanwhile, telephones are popular among the administration staff. The preferable form of communication between internal-operational is formal, without denying that informal form ofl communication is also important.